Analysis Of User Satisfaction Of The Haji Pintar Application Using The Pieces Method At The Office Of The Ministry Of Religious Affairs Of Palembang City - prabowo, rachman agung; Agustina, Merry; Sutabri, Tata; Saprina, Iin (Teknik Informatika Universitas Pamulang, 2023)
The purpose of this study is to determine the analysis of user satisfac-tion with the Application Haji Pintar using the PIECES method. This research method is a descriptive method with a quantitative research approach. The population in this study is all students of the Palembang City Ministry of Religious Affairs Office who use the application Haji Pintar as many as 771 Haji Pintar Application users in 2022. The sam-pling technique using random sampling obtained a sample of 30 people. The results of the study The PIECES indicator variable has a relation-ship with user satisfaction seen from the value of Fcalculate 3.437 > Ftable 2.51, so it can be concluded that all variables together have a positive effect on user satisfaction. The value of the satisfaction level of users of the Haji Pintar Application using the PIECES method on application users, seen from the R Square value of 47.3%. Which means that users of the Application Haji Pintar at the Office of the Ministry of Religious Affairs of Palembang City are satisfied with user satisfaction on the data at the Office of the Ministry of Religious Af-fairs of Palembang City.